Problematizing public engagement within public pedagogy research and practice. Issue 6 (2nd November 2017) - Sandlin, Jennifer A.; Burdick, Jake; Rich, Emma
ABSTRACT: In this article, we explore issues related to how scholars attempt to enact public pedagogy (i.e. doing 'public engagement' work) and how they research public pedagogy (i.e. framing and researching artistic and activist 'public engagement' as public pedagogy). We focus specifically on three interrelated issues we believe should be addressed by scholars as they continue to theorize, enact, and analyze public pedagogies in the broader public sphere: (a) power dynamics embedded in individualized versus more collective enactments of public intellectualism; (b) conflicting and complicated conceptualizations of the relationship between the public pedagogue and the public, and how that relationship should be enacted; and (c) ethical issues surrounding the framing of public engagement and activist work under the umbrella of 'pedagogy'.